الشيخ محمد سعيد رمضان البوطي وموقفه مه المستشرقيه - مصطفاوي, الشيماء; حر, مريم; نيهى, نور الهدى (جامعة الوادي university of eloued, 2016)
حتى تٌسنّى للمطّلع أو القارئ مضمون المذكّرة باختصار وف وقت ضئ لٌ، هٌدف هذا الملخص إلى ذكر أهم ما جاء ف هذا البحث باختصار، بدا ةٌ بالتّعرف على الب ئٌة الت عاش ف هٌا الإمام محمد سع دٌ رمضان البوط - رحمه الله - رغم ندرة مادّ تٌها، وافتقارها لكثرة الدّ عاة و العلماء ف هذا العصر، من أمثال هذا الإمام الفاضل ، كما نٌحو نحو نشأته ونسبه و تع لّمه ومجهوداته العلم ةٌ ونشر دعوته وتنوّ ع أسلوبه لل تصدي لدعاوي الاستشراق الذي كاد ضٌ لّل أبناء المسلم نٌ المفتقر نٌ للرّ د على هؤلاء، ح ثٌ كان ناقدا لهم ولدعاو هٌم ومفحما للعد دٌ من شبهاتهم المزعومة وخاصة ف كتبه " لا أٌت هٌ الباطل و غٌالطونك إذ قٌولون، وفقه الس رٌة النبو ةٌّ" وغ رٌها ... ، فكانت طر قٌة رده على المستشرق نٌ هادئة اعتمد ف هٌا على حجج وأدلَّة مقنعة ومدحضة لأقاو لٌهم الباطلة. Abstract: In order to provide the reader with the contents of the graduation note briefly and in a short time, this summary aims at mentioning the most Important of this research briefly, beginning with the know edge of the environment in which Imam Mohammed said Ramadan el Bouti. May God have mercy on him. Lived despite the scarcity of it materiality and lack of many preachers, The scholars of this era such as the Imam El Fadil, also tend its origins, its proportions, its learning, its scientific efforts, the propagation of its vocation, and the diversity of its style to counter the claims of orientalism which almost mislead the sons of Muslims who were not able to respond to them. Of their alleged suspicions, especially in his books, falsehood does not come to him And the jagltonk as they say, and the jurisprudence of the prophet s biography and others…, was the method of his response to Orientalists calm and relied on the arguments and evidence cornicing and refuting their false claims.